Work environment and neck and shoulder pain: the influence of exposure time. Results from a population based case-control study. Issue 3 (1st March 2002) - Fredriksson, K; Alfredsson, L; Ahlberg, G; Josephson, M; Kilbom, Å; Wigaeus Hjelm, E; Wiktorin, C; Vingård, E
Abstract : Objectives: To study associations between long term and short term exposure to different work environmental conditions and the incidence of neck or shoulder pain. The results were obtained as part of the MUSIC-Norrtälje study, which is a population based case-control study conducted in Sweden in 1993–7. Methods: The cases were people from the study base who sought medical care or treatment for neck or shoulder pain. Information on physical and psychosocial conditions in the work environment, currently and 5 years ago, and lifestyle factors, was obtained by self administered questionnaires from 310 cases and 1277 randomly selected referents. Results: Associations between both physical and psychosocial exposures in the work environment and seeking care for neck or shoulder pain were found. The risk patterns differed for the sexes, and risk ratios exceeding 1.5 were more often found among women than among men. Generally, subjects who had experienced a recent increase of exposure were more likely (relative risk (RR) 2.1–3.7) to seek care than those who had been exposed long term (RR 1.5–1.8). Among women, an increased amount of visual display terminal (VDT) work, work above shoulder level, and reduced opportunities to acquire new knowledge, and among men, an increased amount of seated work were associated with neck or shoulder pain. This might indicate short induction periods for neck or shoulder pain for these exposures. However, for repetitive work with the hands and hindrance at work among women, and possibly also local vibrations among men, the induction periods seem to be longer. Interactive effects between factors, both at work and in the family, were found, but only among women. Conclusions: Associations between some exposures in the work environment and seeking care for neck or shoulder pain were found. The high RRs for short term exposure might indicate that for many factors the induction period for neck or shoulder pain is short.